Physical training reduces peripheral markers of inflammation in patients with chronic heart failure - Adamopoulos, S; Parissis, J; Kroupis, C.; Georgiadis, M.; Karatzas,D.; Karavolias, G; Koniavitou,K.; Coats,A.J.; Kremastinos, D.T. (Eur.Heart J., 2001)
AIMS: Previous studies have shown an abnormal expression of cellular adhesion molecules and cytokines in chronic heart failure, which may be related to endothelial dysfunction characterizing this syndrome. Our study investigates the effects of physical training on serum activity of some peripheral inflammatory markers associated with endothelial dysfunction, such as granulocyte-macrophage colony-stimulating factor (GM-CSF), macrophage chemoattractant protein-1 (MCP-1), soluble intercellular adhesion molecule-1 (sICAM-1) and soluble vascular cell adhesion molecule-1 (sVCAM-1) in patients with chronic heart failure. METHODS AND RESULTS: Serum levels of GM-CSF, MCP-1, sICAM-1 and sVCAM-1 were determined in 12 patients with stable chronic heart failure (ischaemic heart failure: 6/12, dilated cardiomyopathy: 6/12, New York Heart Association: II-III, ejection fraction: 24+/-2%) before and after a 12-week programme of physical training in a randomized crossover design. In addition, the functional status of chronic heart failure patients was evaluated by using a cardiorespiratory exercise stress test to measure peak oxygen consumption. Physical training produced a significant reduction in serum GM-CSF (28+/-2 vs 21+/-2 pg. ml(-1), P<0.001), MCP-1 (192+/-5 vs 174+/-6 pg. ml(-1), P<0.001), sICAM-1 (367+/-31 vs 314+/-29 ng. ml(-1), P<0.01) and sVCAM-1 (1247+/-103 vs 1095+/-100 ng. ml(-1), P<0.01) as well as a significant increase in peak oxygen consumption (14.6+/-0.5 vs 16.5+/-0.5 ml. kg(-1)min(-1), P<0.005). A significant correlation was found between the training-induced improvement in peak oxygen consumption and percentage reduction in soluble adhesion molecules sICAM-1 (r=-0.72, P<0.01) and sVCAM-1 (r=-0.67, P<0.02). CONCLUSION: Physical training affects beneficially peripheral inflammatory markers reflecting monocyte/macrophage-endothelial cell interaction. Training-induced improvement in exercise tolerance is correlated with the attenuation of the inflammatory process, indicating that inflammation may contribute significantly to the impaired exercise capacity seen in chronic heart failure
Keywords: Adult; Aged; Analysis of Variance; Biomarkers; Cardiac Output,Low; Cardiomyopathy,Dilated; Cell adhesion molecules; Chronic Disease; Cross-Over Studies; Cytokines; Exercise Therapy; Greece; Humans; immunology; Middle Aged; physiology; Regression Analysis; rehabilitation